Orders of magnitude reduction in the thermal conductivity of polycrystalline diamond through carbon, nitrogen, and oxygen ion implantation. (February 2020) - Scott, Ethan A.; Hattar, Khalid; Braun, Jeffrey L.; Rost, Christina M.; Gaskins, John T.; Bai, Tingyu; Wang, Yekan; Ganski, Claire; Goorsky, Mark; Hopkins, Patrick E.
Abstract: Despite the exceptional thermal and mechanical functionalities of diamond, its superlative properties are highly subject to the presence of point defects, dislocations, and interfaces. In this study, polycrystalline diamond is ion implanted with C 3+, N 3+, and O 3+ ions at an energy of 16.5 MeV, producing an amorphous layer at the projected range and a damaged crystalline region between the surface and amorphous layer. Using time-domain thermoreflectance in combination with thermal penetration depth calculations based upon the multilayer heat diffusion equation, it is determined that reductions in the thermal conductivity can span nearly two orders of magnitude while still maintaining a polycrystalline structure within the regions thermally probed. Dynamical diffraction simulations of high-resolution x-ray diffraction measurements demonstrate the formation of a strained layer localized at the end of range, with much lower levels of strain near the surface. Furthermore, within the polycrystalline region above the amorphous layer, the average number of displacements- per -atom from the ion irradiation is found to be < 1 %, with mass impurity concentrations much less than 1%. These low defect concentrations within the thermally probed region demonstrate the remarkably large impact that dilute levels of defects from the ion implantation can have on the thermal conductivity of diamond. Graphical abstract: Image 1